Research and Design of Optimal Solution for Network Traffic Anomaly based on Multi-objective Decision Algorithm. Issue 1 (1st February 2022) - Yan, Yiying; Dang, Yijie; Zhang, Shulin; Li, Yang; Li, Zhihong; Le, Xinyi; Yu, Haobo
Abstract: To help maintainers recover from network outages caused by network traffic anomalies, the paper proposes an optimal solution for network traffic anomaly based on multi-objective decision algorithm. It is achieved by combining network traffic anomaly detection with multi-objective decision algorithm, while meeting the objectives of the shortest recovery time, the minimum reduction of security protection and the maximum consistency with the original mode.